5′-Adenosine Monophosphate-Induced Hypothermia Attenuates Brain Ischemia/Reperfusion Injury in a Rat Model by Inhibiting the Inflammatory Response. (22nd March 2015) - Miao, Yi-Feng; Wu, Hui; Yang, Shao-Feng; Dai, Jiong; Qiu, Yong-Ming; Tao, Zhen-Yi; Zhang, Xiao-Hua
Abstract : Hypothermia treatment is a promising therapeutic strategy for brain injury. We previously demonstrated that 5′-adenosine monophosphate (5′-AMP), a ribonucleic acid nucleotide, produces reversible deep hypothermia in rats when the ambient temperature is appropriately controlled. Thus, we hypothesized that 5′-AMP-induced hypothermia (AIH) may attenuate brain ischemia/reperfusion injury. Transient cerebral ischemia was induced by using the middle cerebral artery occlusion (MCAO) model in rats. Rats that underwent AIH treatment exhibited a significant reduction in neutrophil elastase infiltration into neuronal cells and matrix metalloproteinase 9 (MMP-9), interleukin-1 receptor (IL-1R), tumor necrosis factor receptor (TNFR), and Toll-like receptor (TLR) protein expression in the infarcted area compared to euthermic controls. AIH treatment also decreased the number of terminal deoxynucleotidyl transferase dUTP nick end labeling- (TUNEL-) positive neuronal cells. The overall infarct volume was significantly smaller in AIH-treated rats, and neurological function was improved. By contrast, rats with ischemic brain injury that were administered 5′-AMP without inducing hypothermia had ischemia/reperfusion injuries similar to those in euthermic controls. Thus, the neuroprotective effects of AIH were primarily related to hypothermia.